National Cinematograph and National Mind-Set - Eduard O. Krank (Publishing house "Sreda", 2020)
The article is devoted to the problem of national cinematograph in the conditions of the dominance of mass cinema products at the market, especially the American film industry. Paradigms and criteria in the definition of national (ethnic) cinema are presented. The aim of the article is to confirm its working hypothesis, which is that the development of national cinematograph becomes significant only when, reproducing by filming their own narratives, imbued with national mind-set, the authors create cinematographic artifacts with their own manner, style, language, which is able to develop and enrich the film language. The descriptive and analytical methodology used in conjunction with the historical and genetic method allows us to come to certain conclusions. These findings consist in the position that such national cinematograph becomes pervasive, which is permeated by the national mind-set and at the same time responds to both ethnic and world cultural challenges, creates national narratives that due to their relevance become meta-ethnic narratives. An analysis of the existing definitions and properties of what should be understood as national cinematograph allows one to discuss the topic of what the essence of national cinema is: in the local and regional desire to establish itself as having a right to exist, or in the meta-ethnic aspect, which allows national cinema to become a direction in cinema. Thus, the necessary property of national cinematograph for its equal existence among others, the author singles out such a feature as the situation of passionarity in which the nation lives. Its mind-set creates its own national narrative, and therefore its own cinema language. The article is the part of a fundamental study on the theory of cinema, in which the main points are categories such as "film narrative", "conventionality of cinematograph" and "film language".